Nutritional Content Of Crispy Egg Sugar Cane (Saccharum edule) - Yuni Selvianti Sari; Vika Yudistina; Sethyo Vieni Sari (Institut Pertanian Bogor, 2026)
Egg sugarcane plants, also known as terubuk or wax vegetables, are a type of flowering vegetable. In Sanggau Regency, egg sugarcane is only processed as a vegetable. Therefore, it is necessary to innovate processed healthy and nutrient-rich snack options with relatively easy processing, one of which is sugarcane crispy eggs. To determine the nutritional content of processed crispy egg sugarcane snacks, a proxy analysis was conducted to determine the nutritional value of sugarcane crispy eggs. The purpose of this study was to analyze the nutritional value of crispy egg sugarcane. The method used in this study had 3 treatment variations, and the tests carried out were proximate analysis, including moisture content tests, ash, protein, fat, and total carbohydrate. The results of the crispy egg sugarcane test showed the highest moisture content in the A3 treatment of 34.885% ± 0.85, the highest ash in the A1 treatment of 4.45% ± 0.77, the highest fat in the A2 treatment of 42.06% ± 6.55, the highest protein in the A3 treatment of 6.46% ± 3.63, and the highest carbohydrate in the A3 treatment of 29.48% ± 14.79. Based on the data of the proximate analysis that has been carried out, it can be concluded that crispy egg sugarcane can be one of the healthy snack options because of the high nutritional value content of this product. Keywords: crispy egg sugarcane, proximate analysis